Kierunki zmian dzialan techniczno-taktycznych zawodników róznych narodowosci na podstawie Mistrzostw Swiata Juniorów Turcja - 2009 w zapasach w stylu klasycznym - Kruszewski, A.; Kuzmicki, S.; Kruszewski, M.; Jagiello, S. (Polish Journal of Sport and Tourism, 2012)
This paper discusses the relationship between the technique implemented during competition and the end result including an attempt to evaluate the technical and tactical preparation of different nationality competitors in Greco-Roman wrestling. The research was conducted during the 2009 Junior World Cup in Turkey. Material and methods. The research material included a video recording posted by the International Federation of Associated Wrestling Styles (FILA) on their website. The material contained recordings of 240 matches. An analysis of 212 matches with competitors from 49 countries was conducted; each team selected one competitor in each weight category (up to 8 competitors in total). Results and conclusions. During the competition there was strong correlation between victory and the execution of the roll-through and the combat zone and result defence, also in the ground position. Competitors from Russia and Iran, who were most successful, winning 6 and 4 medals respectively, obtained an average of 3.18 technical points in each match. Among the sample analysed this was the lowest score, indicating the optimal use of technical and tactical skills by the competitors resulting in a victory.